ANALISIS PERSEPSI KONSUMEN OJEK ONLINE (GF) (Studi Kasus: Royal Plaza) - Ardhyani, Ika Widya; Moch. Anshori; Nikma Yucha; Gusti Adriansyah; Fajar Mauludhani (JISO : Journal of Industrial and Systems Optimization, 2023)
This study aims to determine the quality of service on customer satisfaction at Royal Plaza Surabaya, based on the results of the analysis of five dimensions of service quality in the Servqual model to create quality services and are expected to have an effect on customer satisfaction. The population of the subjects in this study were 700 people, Grabfood customers in the Royal Plaza area, with a sample consisting of 232 people using the clustering sampling technique. The collected data were analyzed on the Servqual scale, which is described in front (gap) of the expected service quality and the reality received by the customer so that it is known. the level of satisfaction contained in the service attribute which consists of five dimensions of Servqual, namely Tangible (Physical Evidence), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Assurance) and Empathy (Empathy). The results of the study indicate that the quality of Grabfood's services has not fully met customer expectations because all attributes have negative values. From the results of the integration of the Servqual method and the measurement of the Cartesian diagram, the dominant attribute is in quadrant I, the Tangible attribute value is -1,5303 the Reliability attribute value is -1,2121 the Responsiveness attribute value is -0.7013 the Assurance attribute value is -0.5065 attribute value Empathy is -0.8983. Therefore, the Company needs to maintain service quality and strive to improve its service quality so that it is optimal and puts attributes that are in other quadrants into quadrant I.   Penelitian ini bertujuan untuk mengetahui penelitian kualitas pelayanan terhadap kepuasan pelanggan di Royal Plaza Surabaya, sehingga didasarkan pada hasil analisa lima dimensi kualitas layanan dalam model Servqual untuk menciptakan pelayanan yang berkualitas dan diharapakan berpengaruh pada kepuasan pelanggan. Jumlah populasi subjek dalam penelitian ini pelanggan Grabfood wilayah Royal Plaza sebanyak 700 orang dengan sampel terdiri 232 orang dengan menggunakan teknik clustering sampling data yang terkumpul dianalisa dalam skala Servqual yang menggambarkan kesenjangan (gap) kualitas pelayanan yang diharapkan dan kenyataan yang diterima pelanggan sehingga diketahui tingkat kepuasan yang terdapat pada atribut layanan yang terdiri dari lima dimensi Servqual yaitu Tangible (Bukti Fisik), Reliability (Kehandalan), Responsiveness (Daya Tanggap), Assurance (Jaminan) dan Emphaty (Empati). Hasil penelitian menunjukkan bahwa, kualitas layanan Grabfood belum bisa sepenuhnya memenuhi harapan pelanggan karena semua atribut memiliki kesenjangan bernilai negatif. Dari hasil Integrasi metode Servqual dan pengukuran diagram kartesius atribut dominan berada pada kuadran I, nilai atribut Tangible sebesar -1,5303 nilai atribut Reliability sebesar -1,2121 nilai atribut Responsiveness sebesar -0,7013 nilai atribut Assurance sebesar -0,5065 nilai atribut Emphaty sebesar -0,8983. Oleh karena itu pihak Perusahaan perlu mempertahankan kualitas layanan dan berupaya untuk meningkatkan kualitas layanannya agar optimal dan meletakkan atribut yang berada pada kuadran lain ke kuadran I.